Traffic [videorecording (DVD)] - Soderbergh, Steven, 1963-; Gaghan, Stephen; Zwick, Edward; Herskovitz, Marshall; Bickford, Laura; Cheadle, Don; Toro, Benicio del, 1967-; Douglas, Michael, 1944-; Guzmán, Luis, 1956-; Quaid, Dennis; Zeta-Jones, Catherine, 1969-; Moore, Simon (Criterion collection, 2002)
Presents a mix of interrelated stories: a Mexican policeman finds himself and his partner caught in an often deadly web of corruption; a pair of DEA agents work undercover in a sordid and dangerous part of San Diego; a wealthy drug baron living in upscale, suburban America is arrested and learns how quickly his unknowing and pampered wife takes over his business; and the U.S. President's new drug czar must deal with his increasingly drug-addicted teenage daughter.